Prevalence of Chemotherapy-Induced Peripheral Neuropathy in Multiple Myeloma Patients and its Impact on Quality of Life: A Single Center Cross-Sectional Study - Selvy, Marie; Kerckhove, Nicolas; Pereira, Bruno; Barreau, Fantine; Nguyen, Daniel; Busserolles, Jérôme; Giraudet, Fabrice; Cabrespine, Aurélie; Chaleteix, Carine; Soubrier, Martin; Bay, Jacques-Olivier; Lemal, Richard; et al. (Frontiers in Pharmacology, 2021)
Bortezomib is a pivotal drug for the management of multiple myeloma. However, bortezomib is a neurotoxic anticancer drug responsible for chemotherapy-induced peripheral neuropathy (CIPN). CIPN is associated with psychological distress and a decrease of health-related quality of life (HRQoL), but little is known regarding bortezomib-related CIPN. This single center, cross-sectional study assessed the prevalence and severity of sensory/motor CIPN, neuropathic pain and ongoing pain medications, anxiety, depression, and HRQoL, in multiple myeloma patients after the end of bortezomib treatment. Paper questionnaires were sent to patients to record the scores of sensory and motor CIPNs (QLQ-CIPN20), neuropathic pain (visual analogue scale and DN4 interview), anxiety and depression (HADS), the scores of HRQoL (QLQ-C30 and QLQ-MY20) and ongoing pain medications. Oncological data were recorded using chemotherapy prescription software and patient medical records. The prevalence of sensory CIPN was 26.9% (95%CI: 16.7; 39.1) among the 67 patients analyzed and for a mean time of 2.9 ± 2.8 years since the last bortezomib administration. The proportion of sensory CIPN was higher among patients treated by intravenous and subcutaneous routes than intravenous or subcutaneous routes (p = 0.003). QLQ-CIPN20 motor scores were higher for patients with a sensory CIPN than those without (p < 0.001) and were correlated with the duration of treatment and the cumulative dose of bortezomib (coefficient: 0.31 and 0.24, p = 0.01 and 0.0475, respectively), but not sensory scores. Neuropathic pain was screened in 44.4% of patients with sensory CIPN and 66.7% of them had ongoing pain medications, but none were treated with duloxetine (recommended drug). Multivariable analysis revealed that thalidomide treatment (odds-ratio: 6.7, 95%CI: 1.3; 35.5, p = 0.03) and both routes of bortezomib administration (odds-ratio: 13.4, 95%CI: 1.3; 139.1, p = 0.03) were associated with sensory CIPN. Sensory and motor CIPNs were associated with anxiety, depression, and deterioration of HRQoL. Sensory CIPN was identified in a quarter of patients after bortezomib treatment and associated with psychological distress that was far from being treated optimally. There is a need to improve the management of patients with CIPN, which may include better training of oncologists regarding its diagnosis and pharmacological treatment.